2020
DOI: 10.1021/acs.jchemed.0c00713
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Learning in Chemistry: Impact of COVID-19

Abstract: Student learning and course performance are often improved when students actively engage with content. However, pedagogical practices that foster active engagement often rely on student−student and student−instructor interactions that may be difficult to adapt to an online environment. Here we describe a Collaborative Learning program that provides such a learning opportunity to self-selecting General and Organic Chemistry students, describe how this program suddenly transitioned to remote learning due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…Making use of videos and audio for capturing live discussion among students engage interest and sustain different modes of student assessments through poll surveys and quizzes. Studies have reported similar applications in higher education learning contexts [3,11,12].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Making use of videos and audio for capturing live discussion among students engage interest and sustain different modes of student assessments through poll surveys and quizzes. Studies have reported similar applications in higher education learning contexts [3,11,12].…”
Section: Discussionmentioning
confidence: 95%
“…There are AI applications which can assess the student submissions too based on text analysis whereby saving time for teachers. Activities like recording of presentations, Inviting feedback from participants via poll survey/chat box, Critical review of responses, Peer feedback and review provides opportunities to learn from the mistakes and correct responses of peers [3,[10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Fulfer et al (2020) also provided Google Docs for each group, allowing the instructor to monitor each group's progress during the session and to enter breakout rooms where evidence of students' misconceptions was observed. Gemmel et al (2020) provided students with collaborative tasks in Canvas alongside a Google Doc, and noted advantages in being able to include vivid colour and video files more easily than when delivering paper-based tasks in class. In this example, students were assigned specific roles in each group, and their work was monitored to identify when intervention was needed during the session.…”
Section: Breakout Rooms In Chemistry Teaching During the Pandemicmentioning
confidence: 99%
“…Second, we use a vetted lens, Self-Determination Theory, to model and understand how LAs were motivated in their growth and abilities to serve undergraduate STEM learners in a period of rapid change and transition in their professional modality of serving those learners. And third, this article directly addresses the real-time challenges in supporting undergraduate STEM education (Forakis et al, 2020 ; Griffiths, 2020 ), through LA programs (Emenike et al, 2020 ; Gemmel et al, 2020 ), during the current challenge of the COVID-19 pandemic and for future interruptions to come.…”
Section: Introductionmentioning
confidence: 99%